2018
DOI: 10.1002/hyp.13220
|View full text |Cite
|
Sign up to set email alerts
|

Strontium isotope identification of water mixing and recharge sources in a river system (Oder River, central Europe): A quantitative approach

Abstract: This study uses Sr isotope composition (87Sr/86Sr) and Sr content of waters of the Oder, one of the largest rivers in central Europe, to fingerprint natural and anthropogenic contributions to its Sr budget and to evaluate water mixing processes in its hydrological system. It also demonstrates a simple method of quantifying natural and anthropogenic Sr inputs in the watershed. The method has potential for environmental and archaeological research because past Sr geochemistry of river water can easily be reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
10
0
3
Order By: Relevance
“…Unfortunately, the Po plain is one of the most intensely exploited regions of Europe, with extremely few uncultivated, non-urbanized areas. A very recent detailed Sr isotope survey in Poland [82,83] showed that the modern biosphere (animals) and hydrosphere (surface waters) can be contaminated by anthropogenic strontium derived from agriculture, industrial and municipal sources. For that reason, comparison of multiple sample types is necessary to achieve a robust isoscape.…”
Section: Geology Of Northern Italy and Biologically Available Strontimentioning
confidence: 99%
“…Unfortunately, the Po plain is one of the most intensely exploited regions of Europe, with extremely few uncultivated, non-urbanized areas. A very recent detailed Sr isotope survey in Poland [82,83] showed that the modern biosphere (animals) and hydrosphere (surface waters) can be contaminated by anthropogenic strontium derived from agriculture, industrial and municipal sources. For that reason, comparison of multiple sample types is necessary to achieve a robust isoscape.…”
Section: Geology Of Northern Italy and Biologically Available Strontimentioning
confidence: 99%
“…Радиогенные изотопные отношения стронция 87 Sr/ 86 Sr широко используются для выявления источников стронция и исследования его поведения в (био)геохимических циклах. Так, изотопы стронция являются надежным инструментом идентификации взаимодействия водных бассейнов и водоносных горизонтов в различных гидрологических системах (поверхностные, подземные воды) [Frost, Toner, 2004;Zieliński et al, 2018]. В экологических исследованиях изотопы стронция маркируют антропогенный вклад от минеральных удобрений, рудничных, промышленных сточных и муниципальных канализационных вод, а также жидкостей гидроразрыва [Zieliński et al, 2018].…”
Section: Introductionunclassified
“…Так, изотопы стронция являются надежным инструментом идентификации взаимодействия водных бассейнов и водоносных горизонтов в различных гидрологических системах (поверхностные, подземные воды) [Frost, Toner, 2004;Zieliński et al, 2018]. В экологических исследованиях изотопы стронция маркируют антропогенный вклад от минеральных удобрений, рудничных, промышленных сточных и муниципальных канализационных вод, а также жидкостей гидроразрыва [Zieliński et al, 2018]. Отношения 87 Sr/ 86 Sr позволяют подтверждать происхождение или выявлять контрафактную продукцию растительного и животного происхождения (сыр, вино, соки, кофе, оливковое масло), а также минеральную воду.…”
Section: Introductionunclassified
“…Минералы в породе имеют различные отношения Rb/Sr, а, следовательно, различные изотопные отношения стронция (Lee et al, 2011). Поскольку изотопное фракционирование стронция при геохимических процессах можно считать пренебрежимо малым, отношения 87 Sr/ 86 Sr широко используются для исследования взаимодействия вода-порода в подземных, термальных и речных водах (Shand et al, 2009;Lee et al, 2011;Loges et al, 2012;Zieliński et al, 2018). Изотопный состав стронция в воде зависит только от растворения минералов и ионообменных реакций: при течении через водоносный горизонт вода постепенно приобретает 87 Sr/ 86 Sr отношение пород, с которыми взаимодействует (Frost, Toner, 2004).…”
Section: Introductionunclassified